Analysis of mRNA and Protein Levels of CAP2, DLG1 and ADAM10 Genes in Post-Mortem Brain of Schizophrenia, Parkinson’s and Alzheimer’s Disease Patients - Di Maio, Anna; De Rosa, Arianna; Pelucchi, Silvia; Garofalo, Martina; Marciano, Benedetta; Nuzzo, Tommaso; Gardoni, Fabrizio; Isidori, Andrea M.; Di Luca, Monica; Errico, Francesco; De Bartolomeis, Andrea; Marcello, Elena; et al. (International journal of molecular sciences, 2022)
Schizophrenia (SCZ) is a mental illness characterized by aberrant synaptic plasticity and connectivity. A large bulk of evidence suggests genetic and functional links between postsynaptic abnormalities and SCZ. Here, we performed quantitative PCR and Western blotting analysis in the dorsolateral prefrontal cortex (DLPFC) and hippocampus of SCZ patients to investigate the mRNA and protein expression of three key spine shapers: the actin-binding protein cyclase-associated protein 2 (CAP2), the sheddase a disintegrin and metalloproteinase 10 (ADAM10), and the synapse-associated protein 97 (SAP97). Our analysis of the SCZ post-mortem brain indicated increased DLG1 mRNA in DLPFC and decreased CAP2 mRNA in the hippocampus of SCZ patients, compared to non-psychiatric control subjects, while the ADAM10 transcript was unaffected. Conversely, no differences in CAP2, SAP97, and ADAM10 protein levels were detected between SCZ and control individuals in both brain regions. To assess whether DLG1 and CAP2 transcript alterations were selective for SCZ, we also measured their expression in the superior frontal gyrus of patients affected by neurodegenerative disorders, like Parkinson’s and Alzheimer’s disease. Interestingly, also in Parkinson’s disease patients, we found a selective reduction of CAP2 mRNA levels relative to controls but unaltered protein levels. Taken together, we reported for the first time altered CAP2 expression in the brain of patients with psychiatric and neurological disorders, thus suggesting that aberrant expression of this gene may contribute to synaptic dysfunction in these neuropathologies.